Robotic post-chemotherapy retroperitoneal lymph node dissection - Simone Vernez; Jonathan Yamzon; Ali Zhumkhawala (Urology Video Journal, 2024)
Background: Post- chemotherapy retroperitoneal lymph node dissection is a technically complex surgery due to significant fibrosis causing dense adherence of nodal tissue and any residual masses to the major vessels. While open- retroperitoneal lymph node dissection (O-RPLND) remains the standard of care in stage I non-seminomatous germ cell tumor and patients with post-chemotherapy masses greater than 1 cm, minimally invasive approaches such as laparoscopic and robotic have become more wide-spread in high volume centers over the past decade. Early research confirms the safety and early oncologic efficacy of post-chemotherapy robotic retroperitoneal lymph node dissection (R-RLPND), demonstrating comparable nodal yield, shorter operative times, lower estimated blood loss, shorter length of stay, and fewer overall post- operative complications. Methods and results: At City of Hope, we are performing both primary and post-chemotherapy XI R- RPNLD on select patients. For post-chemotherapy RPLNDs, a bilateral retroperitoneal lymph node dissection is performed according to standard templates. Patient preparation, positioning, and port position is demonstrated. The steps of the operation, including gonadal vein dissection, bowel mobilization and suspension with Keith needles, paracaval, inter-aortic, and para-aortic dissections are showed. Post-operative care is discussed. Conclusion: Post-Chemotherapy R-RPLND is feasible and safe. Patients are commonly able to discharge either same day or on post-operative day one.